NCMP-16. MANAGEMENT AND LONG-TERM OUTCOMES OF PATIENTS WITH RECURRENT STROKE-LIKE EPISODES AFTER CRANIAL RADIOTHERAPY. (12th November 2021) - Neth, Bryan; Lachance, Daniel; Uhm, Joon; Ruff, Michael
Abstract: Stroke-Like Migraine Attacks after Radiation Therapy (SMART) is a descriptive clinical entity consisting of transient hemispheric dysfunction. We were interested in pragmatic management patterns for patients with Recurrent Stroke-Like Episodes (R-SLE) of transient negative neurologic symptoms after cranial radiotherapy (RT) to define optimal management strategy and assess long-term outcomes. We conducted a retrospective review of all patients with recurrent negative neurologic symptoms after cranial RT who were treated at Mayo Clinic (Rochester), with follow-up extending until February 2021. Descriptive statistics and Chi-Square analysis was performed to assess for differences between patients with clinical cessation of symptoms, death, progressive encephalopathy and therapeutic class, patient and primary treatment characteristics (i.e. whole brain RT). We identified 27 patients with R-SLE after RT. 25 patients were included in analyses. Median age at diagnosis was 28.7 years (3.0-65.8 years, SD: 15.0 years). Median time from RT to symptom onset was 14.6 years (3.3-30.5 years, SD: 8.9 years). The most common presentations included hemiparesis (55.6%), hemisensory loss (22.2%), transient visual field loss (33.3%), encephalopathy (18.5%), and aphasia (22.2%). Antiseizure medications were most used for management of R-SLE (92%) followed by anti-platelets (68%), verapamil (52%), statins (48%), glucocorticoids (24%), antivirals (20%), and ACE inhibitors/angiotensin receptor blockers (16%). Beta blockers were not used. Verapamil use was frequently associated with clinical cessation of recurrent events with cessation being achieved in 64.7% of patients on verapamil versus 35.3% not on verapamil (p=0.0638). Other medical interventions did not approach clinical or statistical significance. Progressive encephalopathy was more common in patients without clinical cessation (87.5% vs. 23.5%, p=0.0026). All patients who died at last follow-up had progressive encephalopathy. We found cessation of recurrent negative neurologic symptoms after cranial RT in most patients. Verapamil use was associated with clinical cessation. Progressive encephalopathy was more common in patients without clinical cessation of recurrent events.